Metamorphosis Of Justice And Benefit: A Critical Evaluation Of The Application Of The Hedonic Calculus Principle In The Standardisation Of Punishments In The 2023 Criminal Code - Apandi, Haerul; Dede Taufik, Hariang; Paskaries, Rudolf; Aritonang, Hariyanto; Haruman, Andi; Durahman, Dani (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
Criminal law reform through the 2023 Criminal Code shows a paradigm shift in criminal punishment in Indonesia from a retributive approach to a more humanistic and benefit-oriented approach. This study aims to evaluate the application of the principle of *hedonic calculus* as a utilitarian instrument in the standardization of punishment, namely assessing legal policies based on their ability to maximize happiness and minimize suffering through indicators such as intensity, duration, certainty, and extent of impact (Bentham, 1789). Using descriptive methods and a qualitative approach through literature studies and analysis of the 2023 Criminal Code, the results of the study show that sentencing standards have accommodated a utility orientation through alternative punishments, an emphasis on offender rehabilitation, and attention to the social impact of sentencing. This approach has the potential to improve crime prevention and social reintegration, but it still faces challenges in maintaining a balance between social utility, the protection of individual rights, and a sense of justice for victims. Therefore, its implementation must be carried out proportionally while upholding human rights and substantive justice.